Direct versus indirect realism : a neurophilosophical debate on consciousness - Smythies, John R. (John Raymond), 1922-; French, Robert E., 1952-; ScienceDirect eBooks (London, United Kingdom : Academic Press, 2018)
Direct versus Indirect Realism: A Neurophilosophical Debate on Consciousness brings together leading neuroscientists and philosophers to explain and defend their theories on consciousness. The book offers a one-of-a-kind look at the radically opposing theories concerning the nature of the objects of immediate perception-whether these are distal physical objects or phenomenal experiences in the conscious mind. Each side-neuroscientists and philosophers-offers accessible, comprehensive explanations of their points-of-view, with each side also providing a response to the other that offers a unique approach on opposing positions. It is the only book available that combines thorough discussion of the arguments behind both direct and indirect realism in a single resource, and is required reading for neuroscientists, neurophilosophers, cognitive scientists and anyone interested in conscious perception and the mind-brain connection.
Part One: Papers Defending Indirect Realism -- The Metaphysical Foundations of Contemporary Neuroscience: A House Built on Sand -- A Defense of Representational Realism -- Is Direct Realism Falsifiable? -- Against the Combination of Materialism and Direct Realism -- The Epistemology of Visual Experience -- Part Two: Papers Defending Direct Realism -- The Virtues of Direct Realism -- Direct Realism, Disjunctivism, and Screening Off -- Perceptual Realism s Fundamental Forms -- A Dilemma for Epistemological Disjunctivism -- Seeing Things: Defending Direct Perception -- Part Three: The Debate -- Critiques of Papers by Indirect Realists by Direct Realists -- Critiques of Papers by Direct Realists by Indirect Realists -- Rebuttals by Indirect Realists -- Rebuttals by Direct Realists -- Postscript.
Includes bibliographical references and index.
Description based on print version record.
Elsevier
Keywords: Consciousness; Realism; Neurosciences -- Philosophy; PHILOSOPHY / Mind & Body; PSYCHOLOGY / Personality; Consciousness; Neurosciences -- Philosophy; Realism; Consciousness; Electronic books